Tailoring the properties of 3d transition metal complexes with different N-cycloalkyl-substituted tetrazoles. (4th June 2021) - Braun, Vanessa; Wurzenberger, Maximilian H. H.; Weippert, Valentin; Stierstorfer, Jörg
Abstract : N -Cycloalkyl-substituted tetrazoles were coordinated with different late 3d transition metal(ii ) salts to give moderately sensitive energetic coordination compounds. Abstract : Three ligands, 1-cyclopropyl-5 H -tetrazole (C3 tz, 1 ), 1-cyclobutyl-5 H -tetrazole (C4 tz, 2 ), and 1-cyclopentyl-5 H -tetrazole (C5 tz, 3 ), were synthesized and used for the design of 19 new energetic coordination compounds (ECC) based on 3d transition metal complexes. By the varying the metal(ii ) centres (Mn 2+, Fe 2+, Cu 2+, and Zn 2+ ), the corresponding anions (nitrates, azides, chlorates, and perchlorates), and the ligands, the characteristics and properties of the ECC could be perfectly tailored to the desired values. All ligands and coordination compounds were extensively characterized regarding their sensitivities towards various influences, such as impact, friction, and electrostatic discharge, and their thermal stabilities were determined. Furthermore, single-crystal X-ray diffraction experiments, infrared spectroscopy (IR), and elemental analysis (EA) were applied for their investigation. Additionally, ligands 1–3 were examined using the superior two-dimensional 1 H– 15 N-HMBC NMR spectroscopy. The iron(ii ) spin-crossover (SCO) complex 19 was investigated by a temperature-dependent magnetic study, allowing the mapping of the spin transition in a temperature-dependent susceptibility curve.